1991
DOI: 10.1111/j.1365-2133.1991.tb14165.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin inflammation induced by reactive oxygen species (ROS): an in-vivo model

Abstract: A model of skin inflammation induced by reactive oxygen species has been established using the hydrogen-peroxide-producing enzyme glucose oxidase. As a means of increasing the half-life of the enzyme and tissue retention polyethylene glycol (PEG) was attached. A rapid inflammatory response occurred consisting of an oedematous, non-erythemic swelling lasting at least 48 h. Histologically, there was an infiltration of the dermis by monocytes and neutrophils, collagen matrix breakdown and damage to the vascular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…A consequence of cholesterol deposition in membranes is a decrease in the permeability of oxygen (Subczynski et al, 1991 (Trenam et al, 1991;Kohler et al, 1999;Maziere et al, 1999;Fubini and Hubbard, 2003). Because perturbations in the permeability of the inner mitochondrial membrane may result in large-amplitude swelling of the mitochondria, rupture of the outer mitochondrial membrane, and release of proapoptotic proteins, we investigated whether CDDO-Me would induce this mPT in isolated mitochondria.…”
Section: Cddo-me Targets Mitochondrial Membrane Permeability 1191mentioning
confidence: 99%
See 1 more Smart Citation
“…A consequence of cholesterol deposition in membranes is a decrease in the permeability of oxygen (Subczynski et al, 1991 (Trenam et al, 1991;Kohler et al, 1999;Maziere et al, 1999;Fubini and Hubbard, 2003). Because perturbations in the permeability of the inner mitochondrial membrane may result in large-amplitude swelling of the mitochondria, rupture of the outer mitochondrial membrane, and release of proapoptotic proteins, we investigated whether CDDO-Me would induce this mPT in isolated mitochondria.…”
Section: Cddo-me Targets Mitochondrial Membrane Permeability 1191mentioning
confidence: 99%
“…is a highly reactive oxygen species (ROS) that can directly damage lipids and proteins and is a precursor to other ROS like H 2 O 2 . Curiously however, in addition to being an essential component of inflammation (Trenam et al, 1991;Fubini and Hubbard, 2003), mitochondrial-derived ROS have also been shown to be necessary for the activation of a variety of transcription factors, including NFB and activating protein 1 (Kohler et al, 1999;Maziere et al, 1999), and in fact, impairment of mitochondrial electron transport or increased antioxidant capacity have been shown to inhibit the activation of NFB by a variety of stimuli (Josse et al, 1998;Azevedo-Martins et al, 2003;Woo et al, 2004). These findings suggest that agents that affect mitochondrial electron transport could also have anti-inflammatory activity by modulating O 2 .…”
mentioning
confidence: 99%
“…9,10) In these studies, skin injury was caused by glucose oxidase as a producer of H 2 O 2 or arachidonic acid. 9,10) Therefore, this is the first report on the effect of topical application of SOD on UVinduced skin damage.…”
Section: )mentioning
confidence: 99%
“…9) On the other hand, Simões et al studied topical application of SOD. 10) In this previous study, mouse ear edema model induced by arachidonic acid was used, and SOD reduced the edema.…”
mentioning
confidence: 99%
“…PEG, a well-known biomaterial (11), was covalently bonded to the fluorescent hydrogel fibers, thereby reducing inflammation (12,13). These PEG-bonded fluorescent hydrogel fibers maintained glucose responsiveness and transmitted fluorescent signals transdermally for an extended period.…”
mentioning
confidence: 99%